THE EFFECT OF HEALTH EDUCATION CONCERING HIV/AIDS TO KNOWLEDGE AND STUDENT ATTITUDES IN CLASS X STUDENTS OF SMA NEGERI 1 TAMBANGAN MANDAILING NATAL REGENCY - Dari, Seri Wulan (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
HIV stands for Human Immunodeficiency Virus, a virus that licenses the immune system obtained by the Immune Deficiency Syndrome (AIDS). Education about HIV / AIDS as the main weapon against HIV / AIDS or reducing the incidence of HIV / AIDS, because there is no treatment or vaccine that can prevent the spread of HIV / AIDS where the biggest risk factor for transmission is heterosexuals as much as 384 cases (52.10%). This research was intended to see changes in education about students' knowledge and attitudes about HIV / AIDS in Class X students of SMA Negeri 1 Tambangan Mandailing Natal Regency in 2020. The type of research was a Quasi Design experiment (quasi-experimental) by making One Group Pretest Posttest research. Sampling using Total Sampling with a total number of respondents equal to a total of 127 students of class X. Respondents were given a pretest questionnaire continued with counseling, and givenquestionnaire again to conduct a posttest on the same day. Data analysis was performed using the Wilcoxon test which previously carried out the previous normality test. An increase in good knowledge from 39 respondents (30.7%) to 115 respondents (90.6%), and an increase in attitudes toward positive attitudes as many as 36 respondents (28.3%) to 116 respondents (91.3%). Wilcoxon test results obtained the(pvalue = 0,000) where 0,000 <0.05 has a significant difference between the knowledge and attitudes of class X students before and the provision of health education assistance. Recomended to management of the SMA Negeri 1 Tambang Mandailing Natal District in carrying out PKPR activities and expected to theHealth Department to carry out health promotion therelated to efforts and to improve HIV / AIDS infected